2011
DOI: 10.1097/wnf.0b013e318206785a
|View full text |Cite
|
Sign up to set email alerts
|

Yi-Gan San for Treatment of Charles Bonnet Syndrome (Visual Hallucination Due to Vision Loss)

Abstract: Yi-gan san may be an effective and safe therapy to control visual hallucination in patients with CBS and should be further tested in double-blind, placebo-controlled trials. Given the design characteristics of this trial, the present findings should be taken cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…An open-label study reported the efficacy of YKS on visual hallucinations due to vision loss in patients with Charles Bonnet syndrome in 2011 33. Three reports have suggested the potential for use in persons with schizophrenia-related diseases 17,19,20.…”
Section: Controlled Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An open-label study reported the efficacy of YKS on visual hallucinations due to vision loss in patients with Charles Bonnet syndrome in 2011 33. Three reports have suggested the potential for use in persons with schizophrenia-related diseases 17,19,20.…”
Section: Controlled Human Studiesmentioning
confidence: 99%
“…Gastrointestinal complaints have been reported in the elderly5,11,13 and the non-elderly;1719,33,34 however, these complaints are mild and transient. Mild elevation of blood liver enzymes was observed in one case 9…”
Section: Adverse Effectsmentioning
confidence: 99%
“…A prospective, single-arm, open-label study reported the efficacy of YKS in treating visual hallucinations in patients with Charles Bonnet syndrome [11]. A prospective, cross-over, open-label study in Huntington's disease patients showed a significant decrease in motor assessment scores following eight weeks of YKS treatment [12].…”
Section: Yokukansan (Yks) Is a Kampo Formula Consisting Of Seven Herbsmentioning
confidence: 99%
“…This result suggests that an adjunction of yokukansan might be effective for treatment-resistant schizophrenia 34. Furthermore, based on an experience of successful treatment of visual hallucination due to vision loss,35 a 4-week, open-label study was initiated to investigate the monotherapeutic effect of yokukansan in treating Charles Bonnet Syndrome (CBS) 36. A significant decrease of visual hallucination was revealed by psychometrics, including the Neuropsychiatric Inventory (NPI), the hallucination subscale of the PANSS, and Clinical Global Impression (CGI).…”
Section: Yokukansanmentioning
confidence: 99%